Clinical characteristics of medically hospitalized youth with anorexia nervosa/atypical anorexia nervosa and premorbid overweight/obesity. Issue 3 (4th May 2023) - Matthews, Abigail; Gordon, Katelyn; Kramer, Rachel; Lin, Jessica; Ziv, Adi
ABSTRACT: Youth with anorexia nervosa (AN) or atypical anorexia nervosa (AAN) and premorbid overweight/obesity are particularly vulnerable to diagnostic delays, yet research about this patient subset is lacking. This study aimed to compare mental health and demographic characteristics of patients with AN/AAN and premorbid overweight/obesity to patients with premorbid normal weight. Retrospective chart review identified 253 patients (aged 10–22) hospitalized for medical complications of AN/AAN between 2013 and 2020, including 29.6% (n = 75) with and 70.4% (n = 178) without premorbid overweight/obesity. Analyses revealed that patients with AN/AAN and premorbid overweight/obesity were more often cisgender male (24% vs. 8.4%), diagnosed with AAN (62.7% vs. 32%), and had lost a greater percent of body weight (29% vs. 16.4%) than premorbid normal weight counterparts. No significant differences were found for illness duration (10.1 months vs 9.3 months), psychiatric comorbidities (42.7% vs. 32.2%) or psychotropic medication use (25.3% vs. 19.2%), past mental health treatment (44.6% vs. 37.5%), or family history of eating disorders (22.7% vs. 20.8%). Our findings suggest that when relying on historical records, patients hospitalized for medical complications of AN/AAN have similar characteristics across the weight spectrum.